2003
DOI: 10.1897/1551-5028(2003)022<0111:caeoat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

CONSTRUCTION AND EVALUATION OF A TRANSGENIC hsp16-GFP-lacZ CAENORHABDITIS ELEGANS STRAIN FOR ENVIRONMENTAL MONITORING

Abstract: A novel integrated transgenic Caenorhabditis elegans strain (PC161) incorporates a double reporter construct with green fluorescent protein (GFP) and lacZ genes fused in-frame into the second exon of the hsp16-1 gene. This construct also includes the Simian Virus 40 (SV40) nuclear localization signal such that the fusion protein accumulates in the nuclei of expressing cells. The PC161 strain was used to monitor the effects of several known stressors, including heat, cadmium, and microwave radiation. The time c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Similar experiments on strain PC161 (an hsp-16.1::GFP:lacZ double reporter strain) [David et al, 2003] revealed a similar but smaller up-regulation after 6 h at 30ºC (data not shown).…”
Section: Resultssupporting
confidence: 61%
“…Similar experiments on strain PC161 (an hsp-16.1::GFP:lacZ double reporter strain) [David et al, 2003] revealed a similar but smaller up-regulation after 6 h at 30ºC (data not shown).…”
Section: Resultssupporting
confidence: 61%
“…This underlines the wide applicability of transgenic strains carrying hsp16::reporter genes [e.g. PC161, David et al, 2003;CL2070, Link et al, 1999PC72, Stringham et al, 1994] as general biomarkers of stress, since the nematode HSP16 proteins provide a first line of defence against multiple stresses. These roles may not necessarily be identical for orthologous small hsp's in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data indicates that fluorescence signals from GFP reporters (e.g. in the hsp16-1::GFP::lacZ double-reporter strain PC161; David et al, 2003) can be measured from as few as 100 worms per well in a 96-well microplate format suitable for high-throughput screening. These features allow extensive replication under near-identical test conditions, which should allow even small responses to be picked up unambiguously.…”
Section: Introductionmentioning
confidence: 99%
“…Other differences between shielded and exposed conditions may contribute to this contrast. (David et al, 2003). All chemicals were Ultrapure grade from Sigma, and plastic disposables were from Nunc Ltd. unless otherwise stated.…”
Section: Introductionmentioning
confidence: 99%